Transobsturator tape (TOT) procedure: the Ipoh experience - Nusee, Zalina; Naidu, A; Ranjudham, SN; Ismail, Hamizah (University Malaya, 2011)
The use of transobturator tape (TOT) for the treatment of stress urinary incontinence (SUI) has gained popularity since it was introduced in 2001. Only few studies have reported that TOT is superior in safety and efficacy when compared to tension free vaginal tape (TVT). This case-series study was conducted to investigate the safety and efficacy of the TOT procedure in patients at Ipoh Hospital. A cross sectional study on patients who underwent TOT procedures from Jan 2006 to Jun 2008 was conducted. Patients were followed-up 1 month, 3 month, 12 month and annually thereafter. Data were retrieved from patients‟ records based on the standard pre-operative assessment sheet and follow up record. Interviews were then made via telecommunication to assess the patients‟ progression and satisfaction using a validated questionnaire. Fifty-two subjects (n=52) were recruited. The mean age was 54.2 ± 10.6 years with the median follow up time of 19 months. Majority of cases (n=46; 88.5%) had concomitant pelvic organ prolapse (POP), while only 2 (3.8%) had an isolated stress urinary incontinence (SUI). Pre-operatively, only 16 patients (30.8%) were diagnosed with mixed urinary incontinence (MUI) and 24 patients (46.2%) had over active bladder symptoms (OAB) which include increased frequency and urgency. The objective cure rate for SUI was 42 (80.7%), 3 (5.8%) failed while 7 (13.5%) improved. Complications were limited to minor conditions and was only observed in four patients: one case (1.9%) of acute urinary retention, three (5.7%) had prolonged indwelling catheter more than 3 days and one (1.9%) each for mesh erosion, hematoma, urinary tract infection (UTI) and wound infection. Cure rate for MUI, frequency and urgency were 37.4%, 70.8% and 54.2% respectively. De novo urgency was noted in three (n=3: 5.7%) cases while (n=3: 5.7%) required revision of the tape. Forty-nine women (n=49: 94.2%) were satisfied with the procedure. TOT procedures significantly improve OAB symptoms with high patient‟s acceptance rate and no serious operative complication.